Paleocene beds of the Liburnia Formation in Čebulovica (Slovenia, NW Adriatic - Dinaric platform) - Ogorelec, Bojan; Drobne, Katica; Jurkovšek, Bogdan; Dolenec, Tadej; Toman, Martin (Geologija, 2001)
The Liburnia deposits have been studied in a 150 m thick succession in vicinity of Čebulovica, on NW part of the Adriatic-Dinaridic carbonate platform. The studied section is exposed in road-cut of the motor-way Ljubljana - Koper (Trieste). The alternation of brackish deposits with characeans and marine sediments with dasycladaceans and foraminifera is the main feature of the succession. The marine sediments were deposited in intertidal settings of shallow-water ramp and Coastal lagoons. About 60 emersions with typical structures on contact bedding planeš and microcodium (Paronipora) were registered. Owing to different stable isotope composition of δ13C and δ18O three types of limestone: marine, brackish and that one with freshwater influence were recognised. They were deposited at water temperature riching 27° to 30° C. Limestone from the lower part of the succession (Danian, SBZ 1) contains characeans, Lagynophora, gastropods, algae Aeolisaccus barattoloi De Castro along with sporadic occurrences of foraminifera Bangiana hanseni (n.gen. n. sp.). In the upper part of the section (Selandian, SBZ 2) numerous algae Decastoporella tergestina Barattolo, Drobnella slovenica Barattolo, Hamulusella liburnica (Buser et Radoičić), Microsporangiella buseri Barattolo, Cymopolia spp. occur, while characean-bearing horizons are rare. The limestones with marine influences contain foraminifera Kayseriella decastroi Sirel and Haymanella paleocenica Sirel, along with textulariids, valvulinids and rare rotaliids. The limestones of Maastrichtian age with Rhapydionina liburnica Stache form the base of the studied section. To overlying deposits, Thanetian in age (SBZ 3, SBZ 4) were attributed by foraminifera Miscellanea juliettae villattae Leppig, Assilina yvettae Schaub, A. azilensis (Tambareau), Lacazina blumenthali Reichel et Sigal, Pseudolacazina donatae (Drobne) and Discocyclina sp. The youngest deposits are alveolinid-nummulitid limestones with Alveolina daniensis Drobne of Early Ilerdian age (SBZ 6). In the Čebulovica section the correlation between marine fauna and non-marine flora permitted to establish more than 5 million years of the Liburnia Formation deposition after the K/T boundary till Selandian. In the succession the Late Paleocene transgression or the sea level change is reflected. This Thanetian to Ilerdian transgression connected the sedimentary areas in the northern margin of Tethys. Characeans and foraminifera allow the correlation westward to Pyrenees, while dasycladaceans and foraminifera eastward across Herzegovina, Apulia, Cephalonia Island and Greece to Turkey.